Orographic Effects on Berry Morphology and Chemical Composition of Carignan and Grenache Noir Grapes - Sánchez-Ortiz, A.; Castro-Nadal, J.; Lampreave, M.; Mateos, M.A.; Mateo-Sanz, J.M.; Sok, V. (South African Journal of Enology and Viticulture, 2023)
A variation in the climatic parameters of an orographic vineyard influences the growth and development of vines and grapes. Understanding the effects of this is highly beneficial in determining how viticulture practices can be modified to enhance grape quality. The aim of this study was to assess the effects of in-row grape position, altitude and vigour on berry morphology and grape maturity. The effects of vigour, altitude and in-row grape position on berry weight and diameter, titratable acidity, pH and sugar concentration of Carignan and Grenache noir grapes grown in a vineyard located in Priorat were investigated in the 2021 vintage. The results show that Carignan grapes with a lower vigour demonstrated a higher sugar concentration, berry weight and diameter, as well as lower titratable acidity, while the Grenache noir grapes with a lower vigour achieved only a higher sugar concentration. The grapes at high altitude had a higher sugar concentration in Carignan and higher titratable acidity in Grenache noir. Outer-row grapes of Carignan were characterised by lower titratable acidity and a higher sugar concentration, berry weight and diameter, while the outer-row grapes of Grenache noir displayed lower berry diameter, and a higher pH and sugar concentration. Vigour and in-row grape position have stronger effects on berry morphology and chemical composition than altitude. Sugar concentration is more susceptible than other parameters to be influenced by variability in the vineyard conditions.